P56 | HISTOLOGICAL PROFILE OF INACTIVE UNILATERAL CONDYLAR HYPERPLASIA: EVIDENCE OF BORDERLINE TISSUE ACTIVITY (European Journal of Histochemistry)
Unilateral condylar hyperplasia (UCH) is a rare condition affecting mandibular symmetry and temporomandibular joint function1. While “active” UCH is marked by ongoing growth and histological changes, the “inactive” form is traditionally considered stable and without evident metabolic activity2. However, few studies have addressed its microscopic features. In this study, we analysed 15 condylar specimens from patients diagnosed with inactive UCH via SPECT/CT, using quantitative criteria3. Samples were examined through hematoxylin and eosin, Masson’s Trichrome staining, and immunofluorescence for Collagen I/II, MMP-2, MMP-9, RANK, and Osteocalcin. Histologically, we observed thickened hypertrophic cartilage layers and irregular cartilage–bone interfaces, including downward expansions of chondrocytes into bone tissue. Immunofluorescence showed moderate to intense expression of collagen type II, MMP-2, and osteocalcin, as well as RANK-positive osteoclasts near the cartilage–bone border. These findings are consistent with prior microstructural characterizations of condylar tissue remodeling. Our results suggest that, despite being classified as inactive, residual biological activity persists in condylar tissues. This “borderline” state may predispose to reactivation or indicate a slow-progressing pathology.